2022
DOI: 10.1021/acs.jafc.2c06099
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Disulfide-Bonded Thiols in Malt and Hops as the Precursors of Thiols in Beer

Abstract: Disulfide-bonded thiols in malt and hops were first identified as possible precursors of thiols in beer. The presence of disulfide-bonded 3-mercaptohexan-1-ol (3MH) was confirmed in malt and hops by observing an 8.9–9.9 times increase in the 3MH concentration in hopped water and unhopped wort after the reduction using tris­(2-carboxyethyl)­phosphine (TCEP), a reducing agent specific for disulfide bonds. The presence of disulfide-bonded 4-mercapto-4-methylpentan-2-one (4MMP) was confirmed in hops by observing 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It was found to increase slightly over the first 3 h, most probably because of slow malt constituent solubilization, and then to decrease. The fact that the total molar content was lower after 24 h than at the start (0.064 mol/L vs 0.084 mol/L) might be due to Cys-3SHol breakdown (by β-lyase) to free 3SHol (not easily measured in such experiments because of rapid oxidation and/or adsorption).…”
Section: Resultsmentioning
confidence: 93%
“…It was found to increase slightly over the first 3 h, most probably because of slow malt constituent solubilization, and then to decrease. The fact that the total molar content was lower after 24 h than at the start (0.064 mol/L vs 0.084 mol/L) might be due to Cys-3SHol breakdown (by β-lyase) to free 3SHol (not easily measured in such experiments because of rapid oxidation and/or adsorption).…”
Section: Resultsmentioning
confidence: 93%
“…Clearly, the thiol component increased in a temperature- and time-dependent manner, suggesting that a higher temperature loading, rather than processing time, was more effective in generating aroma-active free thiols. Recent studies have shown that hops contain S -cysteinyl and S -glutathionyl forms, as well as disulfide conjugates with proteins, peptides, amino acids, and other thiol substances containing sulfhydryl groups, as precursors of aroma-active free thiols. , These conjugates have been shown to generate free thiols through the carbon–sulfur β-lyase activity of yeast . However, since the concentration of free thiols in beer is in the tens to thousands of parts per trillion range and the conjugates in hops are in the parts per million range, the conversion rate of conjugates to free thiols in hops is estimated to be very low.…”
Section: Results and Discussionmentioning
confidence: 99%
“…For example, sulfur dioxide could induce the aggregation of wine thaumatin-like proteins through disulfide bonds between protein molecules . Amino acids, peptides, and proteins with sulfhydryl groups or other thiol substances were assumed to form disulfide bonds with polyfunctional thiols in malt and hops . Additionally, protein aggregates in soy milk are formed via intermolecular disulfide bonds between the polypeptides of glycinin (11S) and α-subunits of β-conglycinin (7S) .…”
Section: Resultsmentioning
confidence: 99%
“…31 Amino acids, peptides, and proteins with sulfhydryl groups or other thiol substances were assumed to form disulfide bonds with polyfunctional thiols in malt and hops. 32 Additionally, protein aggregates in soy milk are formed via intermolecular disulfide bonds between the polypeptides of glycinin (11S) and αsubunits of β-conglycinin (7S). 33 Furthermore, the reduction of aggregates with TCEP to only monomeric species indicates the presence of intermolecular disulfide bonds.…”
Section: Formation Of Phase-transited Glutenin In Solutionmentioning
confidence: 99%